2005
DOI: 10.1007/s10554-005-7514-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Techniques in Nuclear Cardiology for the Assessment of Myocardial Viability

Abstract: The assessment of myocardial viability has become an important aspect of the diagnostic and prognostic work-up of patients with ischemic cardiomyopathy. Although revascularization may be considered in patients with sufficient viable myocardium, patients with predominantly scar tissue should be treated medically. Patients with left ventricular dysfunction who have viable myocardium are the patients at highest risk because of the potential for ischemia but at the same time benefit most from revascularization. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 119 publications
(81 reference statements)
1
54
0
4
Order By: Relevance
“…It was purified as its HCl salt by bubbling anhydrous HCl gas through its solution in anhydrous ether (6.39 g, 78%). 1 …”
Section: Cyano-cyclohexylamine (4)mentioning
confidence: 99%
See 2 more Smart Citations
“…It was purified as its HCl salt by bubbling anhydrous HCl gas through its solution in anhydrous ether (6.39 g, 78%). 1 …”
Section: Cyano-cyclohexylamine (4)mentioning
confidence: 99%
“…The compound was then extracted with 10% MeOH in DCM to afford pure free base 8. 1 Crystals for X-ray structure determination were obtained through recrystallization from methylene chloride/hexane.…”
Section: 8-dithia-1624-diaza-trispiro[525253]pentacosa-1524-mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to SPECT, PET offers several potential advantages, such as: a higher spatial resolution, lower effective dose due to greater counting efficiency, and higher temporal resolution, allowing fast dynamic imaging of tracer kinetics and thus absolute quantification of myocardial perfusion [2][3][4]. These advantage have presumably influenced the results of consecutive studies, confirming the higher sensitivity and specificity of PET [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, cardiac risk assessment is mostly warranted in asymptomatic patients, particularly in those at intermediate risk. It has been suggested that traditional risk assessment may be refined with the selective use of newer imaging methods, such as coronary artery calcium scoring and noninvasive angiography with computed tomography (CT) techniques [1][2][3][4][5][6]. These technologies, which allow quantification of atherosclerotic burden, can predict risk of cardiac events and might provide an approach to more widespread coronary atherosclerosis screening [7].…”
mentioning
confidence: 99%